Dual inhibitor of MDM2 and NFAT1 for experimental therapy of breast cancer: in vitro and in vivo anticancer activities and newly discovered effects on cancer metabolic pathways - Wang, Wei; Aguilar, Marlene; Datta, Sayantap; Alley, Abigail; Tadesse, Meheret; Wang, Xinshi; Gao, Xia; Zhang, Ruiwen (Frontiers in Pharmacology, 2025)
IntroductionThe oncogene MDM2 has garnered attention not only for its role in cancer as a negative regulator of the tumor suppressor p53 but also for its p53-independent oncogenic activities. MDM2 also involves metabolic reprogramming, such as serine metabolism, respiration, mitochondrial functions, the folate cycle, and redox balance. Traditional MDM2 inhibitors blocking the protein-protein binding between MDM2 and p53 have shown limited clinical success in various stages of clinical trials, most likely due to low efficacy, drug toxicity, and drug resistance, highlighting the need for a novel, p53-independent strategy to inhibit MDM2. The present study investigated the antitumor effects of MA242, a novel MDM2 and NFAT1 inhibitor, in breast cancer models.MethodsThe anticancer activity and underlying mechanisms of MA242 were evaluated in vitro using breast cancer cell lines with different p53 backgrounds and in vivo using orthotopic and patient-derived xenograft models.ResultsWe demonstrated that MA242 significantly inhibited cell viability and induced apoptosis in breast cancer cells, regardless of p53 status. Metabolic analysis revealed that MA242 notably disrupted nicotinamide metabolism, modified nucleotide metabolism, and elevated cellular oxidative stress by disturbing the redox balance. Furthermore, in animal models, MA242 reduced MDM2 expression and effectively inhibited tumor growth dependent on MDM2 expression without causing host toxicity.DiscussionThese findings highlight the potential of MA242 as a modulator of cancer metabolism and support its further development as a therapeutic option for aggressive breast cancers.